1998
DOI: 10.1097/00007890-199805150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Severity of Initial Hepatitis C Recurrence as Predictors of Long-Term Liver Allograft Injury1

Abstract: Features at the onset of histologic HCV recurrence predict the natural history of allograft injury; specifically, marked, transient hyperbilirubinemia is associated with the subsequent development of allograft cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 17 publications
1
80
0
Order By: Relevance
“…11,12 In liver transplant recipients, the course of HCV-induced liver injury is accelerated, with HCV recurrence apparent histologically in approximately 50% of HCVinfected transplant recipients and HCV-associated allograft failure leading to death or graft loss in approximately 10% of transplant recipients by the fifth postoperative year. 2,3,7,10,[13][14][15][16][17] Greater pretransplantation levels of viremia have been associated with attenuated patient and allograft survival among HCV-infected liver transplant recipients. 7 The National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) Liver Transplant Database reported that patients with lower levels of hepatitis C viremia (Ͻ1 ϫ 10 6 viral copies/mL) before liver transplantation had a significantly lower risk for mortality and allograft loss compared with patients with greater levels.…”
mentioning
confidence: 99%
“…11,12 In liver transplant recipients, the course of HCV-induced liver injury is accelerated, with HCV recurrence apparent histologically in approximately 50% of HCVinfected transplant recipients and HCV-associated allograft failure leading to death or graft loss in approximately 10% of transplant recipients by the fifth postoperative year. 2,3,7,10,[13][14][15][16][17] Greater pretransplantation levels of viremia have been associated with attenuated patient and allograft survival among HCV-infected liver transplant recipients. 7 The National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) Liver Transplant Database reported that patients with lower levels of hepatitis C viremia (Ͻ1 ϫ 10 6 viral copies/mL) before liver transplantation had a significantly lower risk for mortality and allograft loss compared with patients with greater levels.…”
mentioning
confidence: 99%
“…[1][2][3][4] Recent data suggest that in approximately 20% of HCV-related transplantations, allograft cirrhosis develops within 5 years. [5][6][7][8][9] HCV-related re-OLT increased significantly throughout the early 1990s, 10 but there are no recent prevalence data to show if this trend continues.…”
mentioning
confidence: 99%
“…These include high pretransplant viral load, the occurrence of acute rejection episodes requiring bolus corticosteroids or antilymphocyte therapy, the presence of HCV genotype 1a of 1b, HCV patients who have received organs from older donors, and the development of cytomegalovirus infection posttransplantation. [32][33][34][35][36][37] In addition, one study has suggested that early recurrence and the severity of recurrence are both associated with a poor prognosis. 33 Recurrent hepatitis C can present as an acute hepatitis or, more commonly, has an insidious onset of abnormal liver tests in which portal hepatitis and/or fibrosis are shown on liver biopsy.…”
Section: S65mentioning
confidence: 99%